Hubungan Pengajaran Firman Tuhan Pembina Terhadap Pemahaman Alkitab Anak Youth di Gereja Bethel Tabernakel Alfa Omega Sampit Kalimantan Tengah Tahun 2022-2023 - Zai, Serika; Rombe, Eni; Susilo, David Priyo (Syntax Literate, 2025)
The teachings of Jesus serve as an example for the church to nurture and prepare for the future of the Church as heirs of the Kingdom of God (James 2:5). However, in reality, many parents, elders, and church members neglect the educational patterns and faith-building processes for children and youth. This study aims to assess the level of teaching of the Word of God for the TYF "Youth Light" children, their understanding of the Bible, and the relationship between the two at Bethel Tabernacle Alfa Omega Church in Sampit, Central Kalimantan. Teaching is a process of learning and teaching, where the teacher's role is to manage teaching effectively and dynamically, while the students actively engage in self-transformation. Understanding the Bible for youth is crucial to protect them from false teachings, enhance their wisdom, and enable them towards salvation. This research uses a quantitative method with descriptive and correlational approaches. The results indicate that the level of teaching the Word of God and the understanding of the Bible among youth in this church is very good, with a score of 91%. The third hypothesis test shows a strong correlation between the teaching of the Word of God by the instructor and the understanding of the Bible, with a correlation coefficient of 74.6%. Thus, the teaching of the Word of God by the instructor affects the understanding of the Bible among youth at the church.